Pelatihan Blended Learning Sistem Informasi Mata Pelajaran bagi Guru SMK Islamic Center Baiturrahman Semarang - Theodora Indriati Wardani; Wijayanto Wijayanto; F X Didik Purwosetiyono; Riyanto Riyanto (Perkumpulan Kualitama Edukatika Indonesia, 2025)
The development of technology in the education sector has encouraged the emergence of various innovations in the learning process, one of which is the Blended Learning model that combines face-to-face learning with digital technology. Therefore, the importance of implementing the Blended Learning SIMPEL (Subject Information System) based on Moodle in supporting the learning process in Vocational High Schools. The aim is to analyze, identify, and evaluate the impact of using SIMPEL on the readiness of teachers and schools to conduct technology-based learning sustainably. Therefore, the implementation of Blended Learning SIMPEL training uses a workshop approach that combines theory with direct practice, this approach is designed to equip vocational school teachers with skills in managing digital learning using the Moodle platform as part of the SIMPEL system. To assess the success of the training, an evaluation is conducted comprehensively, based on the level of interactivity, learning structure, and the collaborative potential developed in the classroom.